An analysis of risk factors and current status of depressive mood in mid-to-late adolescence and early adulthood in northern China - Yang, Xueping; Miao, Junxiao; Bai, Yunlong; Li, Lili; Zhuang, Gengsen (Frontiers in Psychiatry, 2024)
Abstract: At present, the incidence of adolescent depression is increasing each year, having a wide and profound impact on adolescents. This study investigated the mood state of mid-to-late adolescents and young adults and analyzed related factors;clarified the incidence of depression, suicide, and self-injurious thoughts/behaviors in this population; and conducted relevant analysis of related factors of depression and anxiety. Study subjects were students aged 14–25 years, from three high schools and one university in Liaoning Province. Study subjects were evaluated using several questionnaires that combined online and offline methods. Specifically, the Self-rating Depression Scale (SDS), Self-rating Anxiety Scale (SAS), Simplified Coping Style Questionnaire (SCSQ), Child Depression Inventory (CDI), the Chinese version of the Spence Child Anxiety Scale (SCAS), and a general questionnaire were utilized. Single-factor ANOVA, t-test, Chi-square, and multiple regression analysis were used to analyze the data. The results showed that, among the 14–17-year-old subjects, the incidence of depression was 336 (14.7%), the incidence of anxiety was 763 (33.5%). Among the 18–25-year-old subjects, the incidence of depression was 34 (8.6%), the incidence of anxiety was 7 (1.8%). In the general questionnaire, 2081 (77.8%) individuals were depressed, 689 (25.8%) had thoughts of self-injury, and 323 (12.1%) had self-injurious behaviors. Among the 14–17-year-old subjects, 1789 (78.46%) were depressed, 689 (30.22%) had self-injury thoughts, and 319 (1.71%) had self-injurious behaviors. Among the 18–25-year-old subjects, 292 (73.92%) were depressed, but 4 (1.01%) had self-injurious behaviors. The incidence of depression and anxiety in adolescents is high, presenting with a certain risk of self-injury. However, age is an important factor in the occurrence of depression and anxiety; among the 18–25-year-old subjects, the incidence of depression (8.6% vs. 4.7%) and anxiety (1.8% vs. 33.5%) was lower than that among the 14–17-year-old population.Through comparative analysis, adolescents aged 14–17 remained at high risk of depression and anxiety. In the analysis of risk factors for depression and anxiety, relationships with classmates, teachers, and parents were reported as important influencing factors of emotional state. Further, a good coping style was found to be protective against depression and anxiety.